The boastful squire in Gil Vicente’s theatre. Recreating an old comic type: the presumptuous soldier - Tavares de Faria, Rui (Boletim de Estudos Clássicos, 2023)
Among the characters that make up the gallery of Gil Vicente’s types, the boastful squire is a comic figure of guaranteed success. The Portuguese author recreates and old comic model, that of the presumptuous soldier, by putting on stage in the farce Quem tem farelos?, in Auto da Índia and in Farsa de Inês Pereira, the character of the boastful squire. In this article, a comparison is made between the elements that characterize the miles gloriosus, as represented in ancient comedy, and the traits that make up the portrait of the Gil Vicente’s squire, as represented in the mentioned plays. This comparison allows us not only to highlight the similarities and differences between the two models, but also to characterize the artistic process to which Gil Vicente submits model based on the classical motifs.